Pengaruh pertumbuhan ekonomi terhadap kemiskinan Kabupaten Tanjung Jabung Timur - Risang Dwi Anggoro; Syaparuddin Syaparuddin; Nurhayani Nurhayani (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2020)
This study aims to determine the economic development of poverty in East Tanjung Jabung Regency. The data is used in this study is secondary data in the form of time series data and economic growth rate in East Tanjung Jabung Regency. The method of analysis is used in this study is a simple regression. The results of this study indicated that significant capital expenditures to the GDP of the food crops sub-sector and the revenue of regency/city in Jambi Province have no significant effect. Likewise, with strong changes in the number of poor people, the percentage of poor, poverty indices, and poverty severity indices have no significant effect. Keywords: Economic growth, Poverty